The Impact of Online Game Users on Student Learning Achievement - Renita Mei Lina; Ine Kusuma Aryani (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
The use of online games has become a significant phenomenon among students, with the potential to impact their academic performance. This research investigates the impact of online game usage on students' academic achievement, focusing on two main aspects: motivation and concentration in learning, as well as cognitive abilities. The discussion outlines key findings from related literature, highlighting both the positive and negative effects of online game usage in educational contexts. Furthermore, the discussion explores effective strategies for integrating online games into learning to enhance students' academic performance. By considering these aspects, this study provides valuable insights for educators, researchers, and stakeholders in the education sector to understand the role of online games in improving students' academic achievement.